Computational fluid dynamics simulation of geared transmissions with injection lubrication. (November 2019) - Liu, H; Link, F; Lohner, T; Stahl, K
In recent years, the computational fluid dynamics method has developed into very useful tools for investigating the oil flow and the no-load losses in geared transmissions. It has neither restriction on the housing shape nor limitations on the lubrication configuration. For this work, a computational fluid dynamics method model based on the finite volume method of a single-stage, injection-lubricated gearbox was built. The influence of different parameters including the injection volume, oil viscosity, and gear speed on the oil supply and distribution were investigated. The results also include a comparison of the simulated no-load losses with empirical no-load loss equations. This work provides first results on computational fluid dynamics method investigations of injection-lubricated geared transmissions and a starting point for comprehensive validation and more complex modeling.